Odpowiedź :
Odpowiedź:
Zad1.
a) 3x+2 =11
3x= 11-2
3x=9
x=3
b) 5x-x=6+3
6x=9
x=9/6 = 3/2
c) 2x+6=x-5
3x=-5-6
3x=-11
x=-11/3
zad2
a) x-7 = 7 - x - 14 +2x
x+x -2x 7+7 - 14
0 =0
b) x-4x+2x+3 = 18-6x
-x +6x =18-3
5x = 15
x = 3
c) 2x+15 = 16+2x
2x-2x = 16-15
0 = 1
d) x/6 - x/4 = x/2 + 7 /*12
2x -3x = 6x +84
-x-6x = 84
-7x = 84
x = -12
Zad3.
-12x^{2} +2x = 0
2x(-6x+1)=0
x=0 i x=1/6
zad4.
7x-x^2+5x+x^2-6=5x+30-x^2+7x
7x-7x -x^2 +x^2 + x^2 +5x -5x -6 -30 =0
0+x^2+0-36=0
x^2 = 36
x=6 lub x=-6
Szczegółowe wyjaśnienie:
Odpowiedź:
1zad
a)3x+2=11
3x=11-2
3x=9 /:3
x=3
b) 5x-3=x+6
5x-x=6+3
4x=9 /:4
x=4/9
c)2(x+3)=x-5
2x+6=x-5
2x-x=-5-6
x=-11
2zad
a)x-7=7-x-14+2x
x-7=-7+x
x= wszystkie liczby spełniają te równania
b)x-4x+2x+3=18-6x
x+3=18-6x
-x+6x=18-3
5x=15 /:5
x=3
c) 2x+15 = 16+2x
2x-2x = 16-15
O=1
d) x/6 - X/4 = x/2 + 7 / 12
2x -3x = 6x +84
-x-6x = 84
-7x = 84
x = -12
3zad.
-12x^2)+2x = 0
2x(-6x+1)=0
x=0 ix=1/6
zad4.
7x-x^2+5x+x^2-6=5x+30-x^2+7x
7x-7x -x^2 + x^2 + x^2 +5x -5x -6 -30 =0
O+x^2+0-36=0
x^2 = 36